Analisis Penerapan Konsep Asset And Libality Management dengan Sistem Perbankan Syariah di Indonesia - Abu Dzar Al-Ghifari; Pani Akhiruddin Siregar (VISA: Journal of Vision and Ideas, 2023)
In banking operations, Asset Liability Management (ALMA) is the main focus in managing commercial banks. As a tool for analyzing and managing banking operations, it is something that is paid attention to by banking practitioners and academics. This research uses a type of library research. Bibliography research is research carried out using a bibliography in the form of books, memos and information from previous research. On the other hand, the method used is storytelling and analysis. This research results that the application of Asset and Liability Management in Islamic Banking is implemented in a special unit called ALCO (Asset and Liability Management Committee). This committee is responsible for planning, organizing and supervising Islamic bank investments. Keywords: Asset Liability Management, Sharia Banking, Systems and Concept